Clinical Profile And CT Severity Score Of Covid-19 Pneumonia At A Tertiary Care Centre: A Retrospective Observational Study (Indian Journal of Public Health Research & Development, 2024)
Background: COVID-19 infection was previously identified as unexplained cause of pneumonia among groups of patients in China. However it turned out to be a different entity as the scientific manifestations evolved from asymptomatic to fever, running nose, cold to severe life-threatening pneumonia. Approximately 20% of the subjects might advance to severe form of infection which require hospital admission and in some elderly patients intensive care treatment becomes mandatory. Objective: The objective of this study was to evaluate the common symptoms in admitted patients with Covid-19 and to assess the association of different co morbidities with CT severity score in such patients. Material and Methods: This was an observational study carried on admitted patients in a tertiary care hospital of Kashmir, India. Results: Most of the participants (66.28%) in our study were males. Common presenting symptoms were fatigue in 91.86%, fever in 69.77%, muscle aches/joint pains in 63.95%, dyspnoea in 54.65%, cough in 53.49%, chills in 52.33% and anosmia in 50.0%. The common co morbidities present among the participants were hypertension in 48.84%, Diabetes in 33.72%, cardiovascular disease in 24.42%, Hypothyroidism in 20.93% and others were less common. The disease was of mild severity (CT severity score 18) in 33.72%. Multivariate analysis showed that hypertension, diabetes, COPD and low SPO2 on admission had definite relationship with the presence of severe forms of COVID-19 infection. Conclusion: The clinical outcome and CT severity score in COVID-19 subjects largely depends on the presence of different co-morbidities in the infected population.